2021
DOI: 10.2147/jmdh.s286960
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Healthcare Professionals Toward Interprofessional Collaboration in Primary Care Settings in a Middle Eastern Country

Abstract: Background Primary healthcare (PHC) setting is regarded as a central pillar to the healthcare system as it tends to be the first point of contact for patients. Interprofessional collaboration between healthcare professionals (HCP) in PHC settings remains unexplored in the Middle East. Aim The objective of this study was to explore the perspectives of HCP in PHC centers towards interprofessional collaboration and to identify the facilitators and the barriers to collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…CI strategy is mostly applied to the construction of corporate culture, through the planning and improvement of corporate image, to achieve the ulti-mate goal of deepening the quality image of the company into the minds of the public [24]. Previous studies related to the integration of CI strategies into nursing quality management (especially nursing quality management in infusion rooms) are fewer, which researchers believe is related to the fact that most researchers have focused more on nursing operations and nursing technology in their studies to the neglect of nursing environment and nursing culture construction [25]. Therefore, in this study, while applying the Six Sigma method to improve the quality of nursing This study demonstrated that the incidence of adverse events such as inadequate hygienic management during infusion, improper management of medical items, infusion operation errors, and unsuccessful completion of infusion were lower in the research group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…CI strategy is mostly applied to the construction of corporate culture, through the planning and improvement of corporate image, to achieve the ulti-mate goal of deepening the quality image of the company into the minds of the public [24]. Previous studies related to the integration of CI strategies into nursing quality management (especially nursing quality management in infusion rooms) are fewer, which researchers believe is related to the fact that most researchers have focused more on nursing operations and nursing technology in their studies to the neglect of nursing environment and nursing culture construction [25]. Therefore, in this study, while applying the Six Sigma method to improve the quality of nursing This study demonstrated that the incidence of adverse events such as inadequate hygienic management during infusion, improper management of medical items, infusion operation errors, and unsuccessful completion of infusion were lower in the research group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“… 21 A recent study in Qatar found that healthcare providers in primary healthcare generally expressed a positive attitude and readiness towards interprofessional collaboration. 22 The study also reported that healthcare providers with previous interprofessional collaboration or interprofessional education experiences would reveal more positive attitudes toward interprofessional collaboration compared to those without previous experiences. However, the public health field, students and professionals, remain under-represented in such IPE studies.…”
Section: Introductionmentioning
confidence: 76%
“…El-Awaisi et al 22 looked at the level of communication among healthcare providers in primary interprofessional care in Qatar. They reported that most participants rated the level of communication as effective, but they argued that this might not be the real picture as nurses usually agree with physicians which made their voices unheard and thus handling ineffective communication.…”
Section: Discussionmentioning
confidence: 99%
“…Interprofessional collaboration is an emerging concept in the MENA region, and is new to the United Arab Emirates (UAE) [ 18 22 ]. Literature from this region has highlighted context-specific barriers to implementation of IPE.…”
Section: Introductionmentioning
confidence: 99%